AB0226 Optimal Management of Foot and Ankle Disease in Rheumatoid Arthritis: Is a T2T Das-Driven Protocol Adequate?. (9th June 2015) - Saeed, A.; Lee, S.; Mumtaz, A.; Mullan, R.; Kane, D.
Abstract : Background: Erosive foot and ankle disease can be a presenting feature in 30-50% of RA patients. Musculoskeletal ultrasonography (MSKUS) is helpful in detecting synovitis with greater sensitivity and specificity than clinical examination. EULAR (European League Against Rheumatism) recommends a treat to target (T2T) protocol for RA. The DAS-28 CRP is currently used in a T2T protocol but does not include assessment of foot and ankle, which are commonly involved in RA. Objectives: This study comprehensively evaluated the effectiveness of a DAS-28 CRP T2T protocol on foot and ankle disease using standardised clinical and functional scores and ultrasound (US) in patients with RA. Methods: 18 consecutive patients attending Rheumatology out-patient clinics with established RA commencing biological treatment as per T2T protocol were selected. Patients were assessed at baseline and six months with ESR, CRP, DAS28, metrology of ankles and feet, Leeds Foot Impact Scale (LFIS) scores and US of feet and ankles (AS Level 1 Ultrasonographer). All relevant clinical and US findings at baseline and 6 months were recorded and analysed. Results: 16 patients (15 females, mean age =47 years, mean disease duration =46 months) completed the study. 2 patients were excluded as they were unable to attend for follow up visit because of concurrent illness. 94% of Patients were on disease modifying anti-rheumatic drugs (DMARDs) prior to commencing biological treatment (Etanercept =8, Adalimumab =5, Abatacept =1, Golimumab =1 and Rituximab=1) for six months. Significant improvements were observed in DAS28 CRP (p<0.001), tender (TJC) (p<0.001) and swollen feet joint count (SJC) p<0.01 in comparison to baseline. Non-significant improvements were demonstrated in feet US (grey and power doppler scores) and LFIS scores (Table 1 ). 60% of DAS-28 remission patients at 6 months showed subclinical disease with LFIS and GSUS. Conclusions: A DAS-28 CRP T2T protocol is effective in managing clinical foot and ankle disease in most RA patients but significantly underestimates synovitis compared to US as a gold standard. US synovitis at foot and ankle is associated with the progression to joint damage. US should be used to define true foot and ankle disease remission. References: Sokka, T., Quantitative assessment of rheumatoid arthritis in standard clinical care: turning clinical care into clinical science. Best Pract Res Clin Rheumatol, 2007. 21(4): p. 653-61. Brown, A.K., et al., Presence of significant synovitis in rheumatoid arthritis patients with disease-modifying antirheumatic drug-induced clinical remission: evidence from an imaging study may explain structural progression. Arthritis Rheum, 2006. 54(12): p. 3761-73. Szkudlarek, M., et al., Ultrasonography of the metatarsophalangeal joints in rheumatoid arthritis: comparison with magnetic resonance imaging, conventional radiography, and clinical examination. Arthritis Rheum, 2004. 50(7): p. 2103-12. Disclosure of Interest: None declared